2018
DOI: 10.2478/foecol-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

The physiological and genetic differences between flycatchers (Ficedula albicollis vs. Ficedula hypoleuca)

Abstract: The paper studies interspecies physiological and genetic differences between the white-collared flycatcher and the pied flycatcher of the genus Ficedula. The fact that the flycatchers are capable of interspecies hybridization is one more reason for particular interest to these species. Using our own-developed method of taking venous blood from the eye’s sinus, we took blood samples from birds in the protected area of Homilshanski Forests, Kharkiv, Ukraine, to study their leukogram patterns. The bird feathers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Sources of DNA in birds that are commonly used for genetic analysis can be obtained through non-invasive such as feathers, eggshells, and feces (Begović et al 2017;Kaunisto et al 2017;Maia et al 2017;Drahulian et al 2018;Rytkönen et al 2019;Peters et al 2020;Demarchi et al 2022). In the present study, DNA was obtained from the feather and eggshell material of the M. maleo bird.…”
Section: Introductionmentioning
confidence: 99%
“…Sources of DNA in birds that are commonly used for genetic analysis can be obtained through non-invasive such as feathers, eggshells, and feces (Begović et al 2017;Kaunisto et al 2017;Maia et al 2017;Drahulian et al 2018;Rytkönen et al 2019;Peters et al 2020;Demarchi et al 2022). In the present study, DNA was obtained from the feather and eggshell material of the M. maleo bird.…”
Section: Introductionmentioning
confidence: 99%
“…The birds simply do not depend on a particular species of insects (Litt et al 2014, Schirmel et al 2016, Hejda et al 2017. Some studies have identified the role of feed for sympatric species (Drahulian et al 2018) and specific features of overlapping trophic niches of different birds (Lagar 2016).…”
Section: Introductionmentioning
confidence: 99%